On the best L2 -approximations of functions by using wavelets - Babenko, V. F.; Zhiganova, G. S. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain the exact Jackson-type inequalities for approximations in L2 (R) of functions f∈ L2 (R) with the use of partial sums of the wavelet series in the case of the Meyer wavelets and the Shannon–Kotelnikov wavelets.